Inventory control analysis using the period order quantity method at CV. Adi Makmur Metalindo - Andri Herlambang; Nita Marikena (LPPM Universitas Potensi Utama, 2025)
The scheduling raw material orders to avoid delays in fulfilling consumer demand can be analyzed using the Period Order Quantity (POQ) method so that the Company can schedule orders optimally and reduce ordering costs to several suppliers. The Company can control inventory and improve the ability to plan the duplication of goods according to consumer needs. The data used in the study is the demand period in January - December 2024. Data collection uses observation and interview techniques with company leaders and owners. After data collection and calculations using the Period Order Quantity method, the calculation results show that the company can make optimal raw material orders to avoid stock shortages when selling is an order made every 14 days with an ordering frequency of 19 pcs each time the order and the Company must have a safety stock of 8 pcs to anticipate an increase in the number of requests or can reorder when the remaining stock of goods is 29 pcs.